Myocardial Scarring and Sudden Cardiac Death in Young Patients with Hypertrophic Cardiomyopathy: A Multicenter Cohort Study - Chan, R.H.; Carlsson, M.; Jablonowsk, R.; Grosse-Wortmann, L. (JAMA Cardiology, 2024)
Importance: The ability to predict sudden cardiac death (SCD) in children and adolescents with hypertrophic cardiomyopathy (HCM) is currently inadequate. Late gadolinium enhancement (LGE) by cardiovascular magnetic resonance (CMR) imaging is associated with SCD events in adults with HCM. Objective: To examine the prognostic significance of LGE in patients with HCM who are younger than 21 years. Design, Setting, and Participants: This multicenter, retrospective cohort study was conducted from April 8, 2015, to September 12, 2022, in patients with HCM who were younger than 21 years and had undergone CMR imaging across multiple sites in the US, Europe, and South America. Observers of CMR studies were masked toward outcomes and demographic characteristics. Exposure: Natural history of HCM. Main Outcome and Measures: The primary outcome was SCD and surrogate events, including resuscitated cardiac arrest and appropriate discharges from an implantable defibrillator. Continuous and categorical data are expressed as mean (SD), median (IQR), or number (percentage), respectively. Survivor curves comparing patients with and without LGE were constructed by the Kaplan-Meier method, and likelihood of subsequent clinical events was further evaluated using univariate and multivariable Cox proportional hazards models. Results: Among 700 patients from 37 international centers, median (IQR) age was 14.8 (11.9-17.4) years, and 518 participants (74.0%) were male. During a median (IQR) [range] follow-up period of 1.9 (0.5-4.1) [0.1-14.8] years, 35 patients (5.0%) experienced SCD or equivalent events. LGE was present in 230 patients (32.9%), which constituted an mean (SD) burden of 5.9% (7.3%) of left ventricular myocardium. The LGE amount was higher in older patients and those with greater left ventricular mass and maximal wall thickness; patients with LGE had lower left ventricular ejection fractions and larger left atrial diameters. The presence and burden of LGE was associated with SCD, even after correcting for existing risk stratification tools. Patients with 10% or more LGE, relative to total myocardium, had a higher risk of SCD (unadjusted hazard ratio [HR], 2.19; 95% CI, 1.59-3.02; P
Keywords: Adolescent; Cardiomyopathy, Hypertrophic; Child; Cicatrix; Cohort Studies; Death, Sudden, Cardiac; Europe; Female; Gadolinium; Humans; Magnetic Resonance Imaging, Cine; Male; Myocardium; Prognosis; Retrospective Studies; Risk Factors; United States; Young Adult; gadolinium; adolescent; adult; age distribution; Article; cardiac muscle; cardiovascular disease assessment; cardiovascular magnetic resonance; child; cohort analysis; confidence interval; controlled study; female; follow up; hazard ratio; HCM Risk Kids score; heart left atrium; heart left ventricle; heart left ventricle ejection fraction; heart left ventricle mass; human; hypertrophic cardiomyopathy; Kaplan Meier method; late gadolinium enhancement imaging; left ventricular wall thickness; major clinical study; male; myocardial disease; myocardial scarring; pediatric patient; Precision Medicine in Cardiomyopathy score; prognosis; proportional hazards model; retrospective study; risk assessment; risk factor; sudden cardiac death; young adult; cine magnetic resonance imaging; clinical trial; complication; diagnostic imaging; epidemiology; etiology; multicenter study; pathology; procedures; scar